2014
DOI: 10.1002/mnfr.201400298
|View full text |Cite
|
Sign up to set email alerts
|

High dose of prebiotics reduces fecal water cytotoxicity in healthy subjects

Abstract: Structurally different prebiotics affect colonic fermentation and gut health in a different way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Indeed, consumption of bread containing AXOS increased fecal and plasmatic SCFA in healthy humans, notably with an increased acetate, propionate and butyrate in healthy adults [50], or only in butyrate [56,90] SCFA are accepted to be crucial executors of diet-based microbial influence on the host health [91]. However, some studies did not observe an alteration of SCFA production after supplementation with AX-rich WBE [92,93], or even have reported reductions in butyrate [49]. These discrepancies could be related to different degrees of polymerization of AX that determines the gut segment where AXOS is fermented.…”
Section: Do Bacterial Metabolites Mediate the Beneficial Effects Of Amentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, consumption of bread containing AXOS increased fecal and plasmatic SCFA in healthy humans, notably with an increased acetate, propionate and butyrate in healthy adults [50], or only in butyrate [56,90] SCFA are accepted to be crucial executors of diet-based microbial influence on the host health [91]. However, some studies did not observe an alteration of SCFA production after supplementation with AX-rich WBE [92,93], or even have reported reductions in butyrate [49]. These discrepancies could be related to different degrees of polymerization of AX that determines the gut segment where AXOS is fermented.…”
Section: Do Bacterial Metabolites Mediate the Beneficial Effects Of Amentioning
confidence: 99%
“…These discrepancies could be related to different degrees of polymerization of AX that determines the gut segment where AXOS is fermented. Low degree of polymerization could induce a proximal AXOS fermentation and absorption of SCFA, resulting in a lack of apparently increased concentration in feces [92].…”
Section: Do Bacterial Metabolites Mediate the Beneficial Effects Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study showed that the cytotoxicity of fecal water can be reduced after the uptake of oligofructose. [18] Besides oligofructose, KGM are also known to reduce colonic toxicity in human and hence prevent colorectal cancer. [10] Cytotoxicity Cytotoxicity is defined as the negative consequences resulting from disturbance with structures and/or processes required for cell survival, proliferation, and function.…”
Section: Fecal Watermentioning
confidence: 99%
“…Using wheat bran extract and oligofructose in a doubleblind, crossover randomized controlled human trial, the presence of this prebiotic resulted in significant reduction in the cytotoxicity of fecal water. [18] In the intestinal barrier modulation of prebiotic and probiotic, intra-epithelial lymphocytes (CD8+) shut the epithelial barrier response to cause cytotoxicity. [28] Commensal microbes and probiotics are assisted by prebiotics to compete for nutrients and binding sites on the cell surfaces of pathogenic organisms.…”
Section: Fecal Watermentioning
confidence: 99%